Analisis Strategi Pemasaran Syariah pada Produk Hijab - Siti Husna Alawiyah; Deden Gandana Madjakusumah; Intan Nurrachmi (Bandung Conference Series: Sharia Economic Law, 2023)
There is no doubt that every company has a unique approach that must be implemented to ensure that every product that is sold is successful and achieves the goals set. There are product, pricing, advertising, and location/distribution strategies. The purpose of these various marketing objectives is to gain benefits for the company and its own consumers. This problem is caused by the increasing number of competitors who make products that are similar to the products being sold and the lack of product marketing experts. When viewed from the price, this product may not be too expensive for the general public. However, because there are several people who market it, the selling price of the product will change. The purpose of this study is to identify the marketing strategies used by the HAS Hijab Convection and to analyze these strategies by considering their compatibility with sharia marketing. The concept of Islamic marketing and general marketing is used in this research framework. This research is a type of qualitative research using field research, or field research. The research method used is descriptive qualitative. Data was collected through interviews and observation. This study found that the HAS Hijab Convection uses sharia principles in its marketing, but has not maximized its selling value. This research shows that the HAS hijab convection has used a general marketing strategy using a marketing mix, which includes product, price, location, and promotion. In buying and selling and promotions, applying the attitudes of Rasulullah SAW such as shiddiq (honest), amanah (trustworthy), fathonah (intelligent), and tabligh (communicative). So, if a transaction shows a violation of a principle such as honesty, then that principle has not been fully implemented in practice.